The Role of Biochemical Markers in Cataractogenesis. Literature Review - L. Alkharki; A. G. Matyuschenko (Oftalʹmologiâ)
Lens transparency is determined by both cellular and subcellular levels of its organization. Abnormalities of its size, uniformity of shape and correct arrangement of the fibers lead to the scattering of light falling on the lens. At the same time, its normal transparent proteins turn into a cloudy, coagulated, insoluble form, and undergo denaturation. Therefore, the preservation of lens transparency is possible only with a certain chemical composition, achieved by a strict balance of all metabolism links. There are many different hypotheses about the disease etiology. It is known that intraocular fluid has a low content of proteins and an increased concentration of chloride-, lactate-, ascorbatanions in its composition, in contrast to blood plasma. It cannot be ruled out that this is due to the selective permeability of the blood–ocular barrier, which consists of non-pigmented epithelial cells of the ciliary body. In addition, the modification of molecular composition and constitutional imbalance in the intraocular fluid often causes of pathological processes development in the anterior segment of the eye. The blood-ocular barrier makes the eye an immune-privileged organ. However, many diseases, surgical interventions and eye injuries can lead to blood-ocular barrier damage. This causes to inflammatory effector cells and molecules inducing a cascade of reactions, which in turn results in irreversible fibrotic changes in the lens substance. In this regard, it becomes necessary to search for new reliable methods of determining the level of certain biochemical agents in intraocular structures, as well as establishing reference values for strategically important biomarkers of cataract development. This review presents modern views on biochemical markers imbalance in the anterior chamber aqueous humor and the lens, which contributes to its substance opacity.